Caro Dr. Marx: carta de uma feminista socialista Dear Dr Marx: a letter from a socialist feminist - Sheila Rowbotham (Cadernos Pagu, 2009)
A autora dessa carta imaginária, Annette Devereux, é uma personagem fictícia, bem como seu marido, Victor, tipógrafo Cartista, e M. e Mme.Ducrocq. Todos os outros personagens mencionados, no entanto, são figuras históricas e a informação sobre eles é apresentada, na ordem em que aparecem, no final da carta. O argumento e as demandas feitas, os eventos políticos descritos, as revistas e a Falange Fourierista em Wisconsin são todas baseadas na realidade histórica. The author of this imaginary letter, Annette Devereux, is a fictional character, along with her husband, Victor, the Chartist typographer and M. e Mme. Ducrocq. However, all the others characters mentioned are historical figures and infomation about them is provided in the order in which they appear at the end of the letter. The arguments and demands presented, the political events described, the journals and the Fourierist Phalanx at Wisconsin are all based on historical reality.